Mbira in urban spaces: mbira making and the multiple contexts of Zvirimudeze mbira ensemble performances in Zimbabwe - Matiure, Perminus (University of KwaZulu-Natal Press, 2020)
This chapter explores the paradigm shift that mbira has experienced in its adoption and adaption in the urban environments of Zimbabwe. It is apparent that there are aspects of mbira that have changed to suit the contemporary environment in a postcolonial framework. The period under discussion is from when Zimbabwe attained its independence (1980) until 2015 and the chapter focuses on Harare, the capital city of Zimbabwe, as well as Gweru the provincial capital of the Midlands province.